Władysław Kuraszkiewicz jako recenzent wydawniczy "Historii języka polskiego" Zenona Klemensiewicza = Władysław Kuraszkiewicz as the editorial reviewer of "Historia języka polskiego" by Zenon Klemensiewicz - Lewaszkiewicz, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Historia języka polskiego" by Z. Klemensiewicz appeared in three volumes between 1961 and 1972. W. Kuraszkiewicz was the editorial reviewer for the first and second volumes. His reviews featured more than 130 comments (not counting those struck out). Among these were critical remarks, proposals for including additional information and editorial corrections. The book`s author rejected most of the reviewer`s proposals while admitting major critical remarks.
Keywords: Klemensiewicz, Zenon (1891-1969); Kuraszkiewicz, Władysław (1905-1997); historia języka polskiego; historia językoznawstwa polskiego; history of Polish language; history of Polish linguistics